If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -7 + 5 = -23 Reorder the terms: -7 + 5 + 7x = -23 Combine like terms: -7 + 5 = -2 -2 + 7x = -23 Solving -2 + 7x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 7x = -23 + 2 Combine like terms: -2 + 2 = 0 0 + 7x = -23 + 2 7x = -23 + 2 Combine like terms: -23 + 2 = -21 7x = -21 Divide each side by '7'. x = -3 Simplifying x = -3
| 6x-6y=18 | | 13-x=13 | | 18a=54 | | 4=-14+y | | 10x+y=6 | | 2(x-5)+x=14 | | 10+3x=x+x+x+2x | | y=12x-155 | | -2=x+5 | | x^2+20=-9x | | -8=0.4z+4 | | 2x-5=3(x+3) | | 1+2(b+6)=5(b-1) | | -20x+3y=18 | | 2(5-2k)=3(1+2k) | | x^2-6x+40=6x+5 | | 3x-x-5=-17 | | x^2+35=0 | | 5(4+6x)=20 | | 12x+13=-4x-8 | | 5(1x+6)=60 | | -4x+7y=-15 | | 7(2x+5)=175 | | 2(f+3)-2=8+2f | | 5x+2x-10=-15 | | 7y-1=2(y+3)-2 | | 0.6x-15=-21 | | 6(5x+1)=96 | | 2(a+11)=5(s+2) | | -3x+1=4 | | x+x+5=4x+1 | | 2(3d+7)=5+6d |